Dinamika Emosi dan Perilaku Self Harm Terhadap Remaja Putri - Lara Pramesti; Cici Presillia; Rista Fahira (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
The phenomenon of self-harm among adolescent girls has shown a significant increase in recent years, in line with the growing emotional, social, and psychological pressures they experience. This study aims to explore the emotional dynamics and underlying factors contributing to self-harming behavior in adolescent girls, as well as the strategies they employ to cope with such pressures. A qualitative approach with a phenomenological method was used, involving participants aged 19–21 years who had prior experiences of self-harm. The findings reveal that negative emotions such as sadness, anxiety, anger, and feelings of worthlessness are the primary triggers for self-harming behavior, which is often used as an outlet for emotional pain that cannot be verbally expressed. However, such actions tend to reinforce a cycle of negative emotions, as feelings of guilt and shame often follow, further deteriorating the adolescents' mental state. In addition to internal factors, external influences such as family conflicts, academic pressures, and exposure to unrealistic standards on social media also play a significant role in driving these behaviors. Therefore, addressing self-harm requires a holistic approach that includes emotional support from family, a supportive social environment, and enhanced mental health literacy among adolescents. With proper intervention and a deeper understanding of emotional dynamics, adolescent girls can develop healthier and more adaptive coping mechanisms to manage life’s challenges.